Análise da viabilidade econômica de implantação de um vinhedo de uvas de mesa no município de Dom Pedrito-RS - (:unkn) unknown (Universidade Federal do Pampa, 2017)
Being in full development of the wine sector in the region of the gaucho campaign in the production of vitis vinifera grapes for elaboration and processing of fine wines, it is observed that there is no production of table grapes destined to the consumption in natura or agroindustry in large scale in the municipality of Dom Pedrito-RS. The implantation of new cultivars with another aptitude for the development of the local wine sector, will bring a greater range of product options, a feasibility project of implantation of table grapes on a larger scale may help in this aspect. The objective of this research is to analyze the economic feasibility of implementing a table grapes vineyard for production and commercial scale in the municipality of Dom Pedrito-RS, with the purpose of generating data to guide decision-making by producers , industry investors and researchers. Thus, the costs for the implantation of a vineyard of seventeen hectares of table grapes in the conducting system were analyzed, being analyzed their economic viability by means of financial indicators, being they Index of profitability; Profitability; Net Present Value (NPV); Point of Equilibrium; Payback; Minimum Attractiveness Rate (TMA) and Internal Rate of Return (IRR). The economic indicators estimated verified the financial viability of the project under analysis.
Keywords: Vitivinicultura; Análise de viabilidade; Uva de mesa; Viticulture; Feasibility analysis; Table grapes; CNPQ::CIENCIAS EXATAS E DA TERRA